A critical Review on Advanced Membrane Bioreactors for Wastewater Treatment: Fouling Reduction and Energy Demand - Tae-Youl Ryu; Jongyeob Won; Hyunki Jung; Hongrae Im (대한환경공학회지)
Objectives Rapid industrialization has highlighted the importance of addressing environmental issues and the increasing demand for water supply. As a result, innovative solutions to improve water circulation management in both public and industrial sectors have been proposed, one of which is the introduction of Membrane Bioreactor (MBR) technology. This study aims to understand the mechanisms and characteristics of membrane fouling in MBR processes and compare the associated energy consumption, with the goal of improving process efficiency and energy performance. Methods In this study, various factors influencing the MBR process were considered to analyze the mechanisms and characteristics of membrane fouling. The impact of fouling on the process was assessed, and energy consumption was compared. Specifically, the power consumption of flat-sheet and hollow-fiber MBRs was analyzed, focusing on the proportion of energy used for microbial treatment and membrane cleaning. The Specific Energy Demand (SED) was calculated to evaluate the energy consumption efficiency of different fouling control methods in MBRs. Results and Discussion In typical MBR processes, 68.0% (flat-sheet) and 53.0% (hollow-fiber) of the power consumption is attributed to air scouring for microbial treatment and membrane cleaning. Notably, 57.0% (flat-sheet) and 36.0% (hollow-fiber) of the power is consumed to supply air for detaching adhered foulants to maintain filtration performance. These results indicate that aeration is a major energy consumer in MBR processes. SED is a critical indicator for assessing the energy consumption of specific fouling control methods, with typical MBR processes having an SED of 0.2-0.3kWh/m3. In contrast, using a non-aerated membrane module with reciprocating inertial force for fouling control reduces SED to 0.005-0.01 kWh/m3, representing a 20-60 fold decrease in energy consumption, highlighting the need for energy reduction. Conclusion This study provides insights into fouling reduction characteristics in MBR processes, suggesting a new paradigm for enhancing the economic feasibility of MBR technology. Applying non-aerated membrane modules to reduce energy consumption can significantly improve MBR efficiency, contributing to energy reduction and environmentally friendly technology development. Therefore, strategies to maximize energy efficiency and minimize environmental impact in MBR processes are essential.